Experimental study of the influence of saturation on the resistivity response of sandstone - He, Xiaolang; Zheng, Xinchao; Pu, Zhiguo; Qin, Wei; Duan, Dongwei; Xie, Peng; Zhang, Qi (Frontiers in Earth Science, 2024)
Studying the changes in electrical resistivity of sandstones under various frequencies and saturation levels is important for addressing many geological problems through electrical prospecting. In this study, we investigated the effect of different frequencies (500 Hz-200 kHz) and saturation levels (0%-100%) on the resistivity of sandstone in the Ordos region. Our research indicates that when the saturation level is low (<40%), the resistivity of the sandstone decreases rapidly. With the increase of saturation level, pore water gradually becomes another major factor affecting resistivity in addition to induced polarization effect. When the saturation level is high (>80%), the resistivity tends to stabilize. Additionally, the resistivity of sandstone decreases with the increase of saturation. Furthermore, with an increase in frequency, the rate of reduction in resistivity gradually slows down, and the resistivity of sandstone decreases under the influence of saturation. This study provides a valuable reference for the practical application of sandstone resistivity in geological prospecting.